Islamic Historiography from Normative Tradition to Critical and Interdisciplinary Approach - Annisa Nur Baeti; Susanti Sangidah; Irfan Musonif; Kholid Mawardi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This article aims to analyze the transformation of Islamic historiography from a normative tradition toward critical and interdisciplinary approaches. Employing a qualitative approach with a literature review method, this study synthesizes and critically examines various scholarly works related to the development of Islamic historiography. The findings indicate that early Islamic historiography was rooted in oral traditions and the codification of hadith, which established an epistemological foundation based on the verification of transmission (sanad) and content (matan). In its classical phase, Islamic historiography was predominantly siyasah-oriented, reflecting the interplay between knowledge production and political power, resulting in elitist and event-centered narratives. Criticism of these limitations led to the emergence of more analytical approaches, most notably articulated by Ibn Khaldun through his concept of social interpretation. In the modern period, Islamic historiography has evolved toward interdisciplinary approaches by incorporating social, cultural, and economic perspectives, including localized contexts such as Indonesian historiography. This study argues that Islamic historiography is a dynamic epistemological construct that has shifted from a normative-descriptive model to a critical-reflective approach in understanding history.